Optimasi Keuntungan Dari Penjualan Brownies Amanda Dengan Menggunakan Program Linear Metode Simpleks - Hasibuan, Cahaya Nabila; Siti, Siti; Simanjuntak, Hoirun Nisyah; Silaen, Siti Humairoh; Ritonga, Irmayanti (Universitas Labuhanbatu, 2024)
The purpose of research on amanda brownies is to calculate the maximum profit from the sale of amanda brownies.as well as for the use of Simplex methods on the constraints experienced by amanda brownies sales business. this study uses one method in linear programming is the Simplex Method.the simplex method was developed by George Dantzing in 1947 (Budianto,Mujiharjo and Umrah 2017). The results of this study obtained the maximum profit (optimal) by using the Simplex Method obtained from the sale of amanda brownies got a maximum profit of Rp.839,717, - production every day.and linear programs, especially simplex methods, can be used and utilized to maximize profits.